Settlement Patterns of the Population Use the Average Nearest Neighbor Method - Tika Widayanti; Tiyas Yulita (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study utilizes the Average Nearest Neighbor (ANN) method to analyze settlement patterns based on population density data across 15 regencies and cities in Lampung Province, Indonesia. ANN is a spatial statistical technique used to determine spatial distribution patterns by calculating the average distance between points, the number of points, and the area of the region. The analysis involved computing the ANN index and z-scores for each regency and city. The results, as shown in the analysis, indicate that the ANN index values are below one, ranging from 0.114 to 0.769, and the z-scores are negative, ranging from -146.719 to -13.235. These findings suggest that the settlement patterns across all studied areas in Lampung Province exhibit a clustered pattern. This implies that densely populated areas do not significantly influence the settlement patterns of less densely populated regions. The study concludes that the population density pattern in Lampung Province is predominantly clustered, reflecting a tendency for settlements to be concentrated in specific areas rather than dispersed.
Keywords: Average Nearest Neighbor; Clustered Patterns; Population Density; Settlement Patterns; Spatial Analysis